2021
DOI: 10.3389/fsurg.2021.693288
|View full text |Cite
|
Sign up to set email alerts
|

Reassessment of Relevance and Predictive Value of Parameters Indicating Early Graft Dysfunction in Liver Transplantation: AST Is a Weak, but Bilirubin and INR Strong Predictors of Mortality

Abstract: Introduction: Early graft dysfunction (EAD) complicates liver transplantation (LT). The aim of this analysis was to discriminate between the weight of each variable as for its predictive value toward patient and graft survival.Methods: We reviewed all LT performed at the Medical University of Innsbruck between 2007 and 2018. EAD was recorded when one of the following criteria was present: (i) aspartate aminotransferase (AST) levels >2,000 IU/L within the first 7 days, (ii) bilirubin levels ≥10mg/dL or (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 29 publications
0
8
0
1
Order By: Relevance
“…It is noteworthy that the majority of EAD grafts in this study met only one EAD criterion, AST > 2000 U/L during the first week post-LT. Fodor et al previously noted that bilirubin and INR have a stronger predictive capacity for patient and graft survival compared to AST [26]. Similarly, Wang et al also noted that EAD outcomes varied by the number of observed criteria, with outcomes of recipients having one criterion being superior to those with two or three criteria [22].…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…It is noteworthy that the majority of EAD grafts in this study met only one EAD criterion, AST > 2000 U/L during the first week post-LT. Fodor et al previously noted that bilirubin and INR have a stronger predictive capacity for patient and graft survival compared to AST [26]. Similarly, Wang et al also noted that EAD outcomes varied by the number of observed criteria, with outcomes of recipients having one criterion being superior to those with two or three criteria [22].…”
Section: Discussionmentioning
confidence: 98%
“…These studies have shown inferior patient and graft survival as well as increased resource utilization such as ventilator days, occurrence of renal failure, and longer hospital length of stay [11][12][13][14][15]. The rising prevalence of EAD with the use of nonconventional grafts, such as those from DCD donors, is arguably expected; however, increasingly favorable outcomes have also been demonstrated with such donors despite the presence of at-risk variables [4,5,18,[24][25][26]. In this series, 31.8% of grafts were from DCD donors and post-transplant outcomes were similar in regard to resource utilization (ICU and hospital length of stay), prevalence of AKI, and patient and graft survival.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, postoperative levels of transaminases are influenced by the perfusion itself and the large volume of perfusate (wash-out) ( 72 ). Additionally, bilirubin and INR seem to have a stronger predictive capacity for patient and graft survival compared to AST, indicating that hepatocyte injury with little involvement of the biliary tree has a more benign course ( 86 ). The usefulness of the current definition of early allograft dysfunction (using peak transaminases in the first week, total bilirubin and INR levels) ( 55 ) in case of livers transplanted after perfusion is unclear and the definition might need revisiting ( 86 , 87 ).…”
Section: Livermentioning
confidence: 99%
“…Further to this, innovative liver graft viability and injury markers have been applied. However, whether they are acceptable predictors of the outcomes after LT remains to be proven ( 2 , 4 , 11 , 12 ). Novel non-invasive methods for the estimation of organ quality during NMP are necessitated.…”
Section: Introductionmentioning
confidence: 99%